Genre invariant of a conspiracy novel - Плетена, Олена Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The purpose of the article is the substantiation of theoretical construct of the research – the genre invariant of the conspiracy novel. It is found that the theoretical construct has the following structure: the genre paradigm of adventure literature, which includes the conspiracy novel; the theoretical model of the genre – its invariant; the precedential text – the conspiracy novel of the "Dan Brown’s type”; the genre typology (versions of modifications). It is proved that the “law of the genre” of the conspiracy novel as a new form of postmodern prose marks genre polyphony. The genre model of an invariant covers three plans: 1) a plan of content, 2) a plan of structure, 3) a plan of perception (according to N. Leiderman). The content plan includes invariant conspiracy motifs that are genre-forming. We consider that the dominant of the structure plan is the space-time organization, which includes the plot, the character system, and inset elements. The quest-chronotype is specific to the conspiracy novel. Its character is determined by the plot unity of search motives, the complex picture of subject-object relations, and the predicate which is a multi-level “maze”. The plot-forming constants of the conspiracy novel are a secret – a conspiracy – an investigation as a targeted search. Due to the genre marker – the secret of the conspiracy, which remains the core of the plot, the world of the novel is divided into “ours” / visible reality and “alien” / invisible reality. The quest-chronotope emerges the receptive plan of the conspiracy theological novel, namely: it helps to identify the reader with the characters, increases interest in the work, establishes a game relationship between the author and the reader, since as a result of a general search they comprehend the truth. The precedent text of the theoretical construct is the conspiracy novel of the “Dan Brown’s type”. The descriptive model of the invariant allows us to trace genre modifications and describe the typology of the conspiracy novel in Ukrainian and American literature. The model performs both theoretical and practical functions – it contributes to the development of methodological approaches and tools for studying mass literature.